Les conventions ACP-EU et les sanctions économiques de l'Union européenne contre les Etats ACP : le cas du Togo - Nikabou, Lantame Jean (Université de Strasbourg, 2013)
L’Accord de Cotonou, signé en juin 2000 entre l’Union européenne et les États d’Afrique, des Caraïbes et du Pacifique (ACP), se caractérise par un respect des droits de l’homme, des normes démocratiques et de l’État de droit d’une part, et la quête d’une conformité des normes aux principes de l’Organisation mondiale du commerce (OMC), d’autre part. En effet, la politique de développement mise en place par l’Europe au profit des États ACP a vu le jour avec le Traité de Rome et la création du Fonds européen de développement au profit des ces pays. Pendant longtemps, le partenariat, essentiellement économique, a octroyé d’énormes avantages aux pays ACP en vue d’assurer leur développement. Depuis bientôt deux décennies que les normes politiques ont été insérées dans ce partenariat, force est de constater que quelques pays, dont le Togo, demeurent toujours réticents quant à l’instauration de réelles réformes démocratiques en vue d’assurer une véritable alternance politique. En dépit des sanctions infligées çà et là par l’Union européenne, ces pays trouvent un appui auprès de la Chine qui mène, avec les pays d’Afrique, un partenariat en toute exclusion de la société civile.
Keywords: ACP; Accord ACP-UE de Cotonou; Accord de Cotonou; Afrique; Chine; Cotonou agreement; Economic partnership between EU and ACP; Partenariat; Partenariat économique; Partnership between China and Africa; Pays ACP; Pays de l'Union européenne; Relations extérieures; Relations économiques internationales; Togo; Traités; UE

La modernisation du cadre budgétaire des pays de l'UEMOA - Zoure, Daouda (Université Paris 1, 2013)
La recherche porte sur la modernisation du cadre budgétaire des pays de l’UEMOA. Il s’agit d’évaluer la portée des réformes budgétaires développées dans chacun de ces pays. On s’est essayé à mettre en évidence la nécessaire mise en place d’une standardisation de certains dispositifs ainsi que d’une adaptation des procédures ayant fait leurs preuves non seulement dans certains États de la zone mais également dans d’autres pays confrontés à des problèmes similaires. On s’est appuyé sur les comparaisons internationales existantes et l’on a évalué la pertinence des solutions proposées notamment par les bailleurs de fonds. This research relates to the transformation of budgetary framework of West African Economic and Monetary Union (WAEMU) countries. It is a question of evaluating the extent of the budgetary reforms undertaken in each respective country. The research has tried to highlight the necessary installation of certain standard devices as well as adapting proven reliable procedures not just for certain zones of specific countries but also other countries confronted with similar issues. This exercise was based on existing international comparisons and the evaluation examined the relevance of the solutions suggested in particular by the financing institutions.
Keywords: Afrique occidentale; Budget framework; Budgetary framework; Contrôle judictionnel; Finance publique; Loi des finances; Processus budgétaire; Public finance; UEMOA; Union économique et monétaire Ouest africaine -- 1990-2020; WAEMU

La régionalisation de la paix et de la sécurité internationales post-guerre froide dans le cadre de la CEDEAO : la construction d’un ordre sécuritaire régional, entre autonomie et interdépendance - Ali Gazibo, Kadidiatou (Université Paris 1, 2013)
Ce travail a pour objectif d'analyser la nature et l'ampleur des tentatives d'institutionnalisation d'un régime régional de sécurité dans le cadre de la communauté des États de l'Afrique de l'Ouest (CEDEAO). Elle part du constat que la fin de la guerre froide et la globalisation ont provoqué un changement dans la nature de la conflictualité et changé la donne pour l'ONU et les grandes puissances dans le domaine du maintien de la paix. Face à la multiplication des conflits internes et régionaux, on observe l'émergence de nouveaux acteurs de sécurité qui leur contestent le monopole des opérations de maintien de la paix et de la sécurité. En Afrique de l'Ouest, sous l'action de la CEDEAO, on assiste à partir de 1990 à la "sécurisation" progressive d'enjeux non militaires (politique, social, économique et environnemental) avec comme objectif, la mise en place d'une communauté de sécurité. En nous appuyant sur les cas empiriques d'interventions de la CEDEAO au Libéria, en Sierra Léone et en Guinée-Bissau entre autres, nous analysons pourquoi et comment la régionalisation des opérations de paix a produit des transformations, notamment une politique d'intégration et une reformulation des enjeux sécuritaires dans la région. Cela nous conduit à appréhender la CEDEAO comme région et comme acteur de sécurité dans le champ des relations internationales. En recourant à différentes approches (fonctionnalistes, constructivistes, réalistes), nous explorons d'une part le processus régional de sécurisation au plan empirique et institutionnel, et d'autre part les difficultés, les apprentissages et les jeux d'acteurs dans le champ des opérations de paix. Dans la mesure où ce dernier est ouvert et investi par différents acteurs, se pose également la question de la coordination de leurs interventions.
Keywords: Afrique occidentale; CEDEAO; Communauté de sécurité; Communauté économique des États de l'Afrique de l'Ouest; Fonctionnalisme (sciences sociales); Institutionalizing; Institutionnalisation; Maintien de la paix; Peacekeeping; Regionalization; Régionalisation; Security community; Sécurité internationale; Sécurité économique

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification

Challenges to political and economic intergration in Africa : A socio-Legal perspective - Mwanawina, Ilyayambwa (North-West University, 2013)
This study is concerned with integration efforts on the African continent. This study sets out to investigate the politico-legal and economic impediments to regional and continental integration efforts in Africa. The documents, processes, and organs of the African Union, as the main continental organisation, are the focal point of this study. In order to achieve this, the study primarily adopted a qualitative approach since the literature involved in this work could not be reduced to a quantitative concept. The study ensured that the premises and the conclusions in this work conform to the principles of reliability and validity and in addition the elimination of bias in this was curtailed by validation and triangulation. This was achieved by the fact that the arguments in this work were not only based on qualitative arguments but, where possible, quantitative data was brought in to validate/ triangulate the qualitative arguments. Evidently, the study would have been incomplete if it did not discuss and evaluate the many regional economic communities that have been established to further the objectives of the Treaty establishing the African Economic Community. One of the major premises that this study discovers is that there is a direct and demonstrable relationship between democracy and economic progress; genuine and sustainable development has to be fostered primarily by securing peace and stability on the African continent. Some of the other key findings of the study include that; a) the ultimate goal of the African Union is full political and economic integration leading to the United States of Africa; b) overlapping memberships to a custom unions are highly detrimental to the state since it has to subscribe resources and political will to two or more different arrangements. c) overlapping memberships cause confusion, inertia and most importantly legal uncertainty thereby stifling trade liberalisation efforts; d) many African states still guard their sovereignty closely and that many perceive that yielding their sovereignty to a continental body is tantamount to losing their independence; e) the African Union infrastructure still lacks supra-national and national institutions that are capable of implementing its values; f) the African Union infrastructure does not contain an institutionalised mechanism for the promotion and management of Union affairs at national level; g) the NEPAD initiatives, the APRM process and the functions of the Peace and Security Council play a positive role in African politico-legal and economic development. It has however been shown that these mechanisms are more reactive than preventative and as such intervene too late in the internal affairs of member states; h) armed conflicts cause a reduction in the per-capita Gross Domestic Product growth rate of a nation experiencing a civil war/ conflicts. i) the African Union has regressed from the original timelines of the African Economic Community. The highest regression being Phase 2 which involves the most critical element of strengthening of African regional integration arrangements and the harmonisation of policies concerned. A thirteen (13) year postponement is noted in this regard. j) Africa's poor intra-trade performance is also attributed to the limited progress among African countries in fostering structural transformation. This structural transformation relates to the building of roads, bridges, railway lines and power grids; In order for the African continent to re-position itself in an attempt to harness the benefits of regional integration, some of the recommendations that the study makes are that; a) the African Union grant supra-national status to institutions of the Union for the equitable and speedy attainment of integration; b) the Union and member states should as soon as possible create mechanisms with decision making powers to manage Union affairs at regional and national level; c) the operationalization of the Pan African Parliament should be pursued with the utmost determination to bring the Parliament to full functionality as a Continental legislative body; d) the operationalization of the African Court of Justice and Human Rights be completed as soon as possible in order to allow the body to function as a fully-fledged continental judiciary. This will ensure that the development of integration jurisprudence from an international law perspective is not delayed. The Court will also pursue the enforcement of Human rights norms and practices; e) the Union should further lead the continent in the following sectors with clear and predictable deliverables; i) the establishment and upgrading of regional land, air, and other means of transportation and communication; ii) the creation of a cross-border power and energy generation and distribution network; iii) the establishment, advancement, and diversification of regional financial and commodity markets; iv) the establishment of a regional higher education system by facilitating wider access through specialization in regional integration; The study further acknowledges that these recommendations are not conclusive since the study of regional integration is still at its infancy and many other ideas on how to strengthen African regional integration still await discovery.

Climate change and Africa : the normative framework of the African Union - Pallangyo, Daniel Mirisho (North-West University, 2013)
There is enough evidence on how climate change consequences will adversely affect Africa despite the fact that it is the continent that has least contributed to the problem. The international climate change regime recognises Africa's vulnerability to climate change and provides for special treatment under the United Nations Framework Convention on Climate Change (the UNFCCC). Thus, the international climate change regime presents an opportunity for African countries to adapt and mitigate the consequences of climate change through the UNFCCC mechanism. However, the international climate change legal regime has not been able to adequately assist African countries to address the consequences of climate change under the vulnerability principle. Although the current international climate change regime requires developed countries to reduce their greenhouse gas (GHG) emissions, Africa needs to take steps itself to address the problem, because it is most vulnerable to the consequences of climate change. The African Union (AU) could play a great role in ensuring that the international climate change regime addresses the consequences of climate change in the region. This could be done through fostering strong African common positions during international climate change negotiations. A strong common position could strengthen African bargaining power and might result in more funding, capacity building and technology development and transfer for adaptation and mitigation programmes under the UNFCCC-Kyoto Conference of Parties. However, reaching a strong common position requires the cooperation of the AU member states. In this context, African regional integration is an opportunity for the AU to foster such cooperation among member states. The Treaty Establishing the African Economic Community (the Abuja Treaty), the Constitutive Act of the AU and the Protocol on the Relations between the AU and Regional Economic Communities (RECs) prioritise regional economic integration and call for states' cooperation, but the call has not yet been heeded. To realise deep and viable African integration, there must be a well-structured institutional and legal framework that defines the relationship between the AU, the AEC and the RECs. African regional integration is also seen as an avenue whereby the AU can create its own regional climate-change regime. In this regard, the AU's and RECs' normative framework on climate change is examined in order to assess whether it adequately integrates climate change issues. This study finds that although Africa is most vulnerable to the consequences of climate change, the AU's and RECs' normative framework on climate change is weak and inadequate to address the problem. The Framework should integrate climate change issues in order to achieve sustainable development. The AU should also ensure that member states ratify the relevant treaties and protocols (the Maputo Nature Convention and the Protocol establishing the African Court of Justice and Human Rights) that have not yet been ratified in order that they may become operational. The Maputo Nature Convention puts sustainable development in the forefront of attention as a reaction to the potentially conflicting environmental and developmental challenges facing the continent (such as climate change), but it is not yet in force. This work finds that human rights law can strengthen the AU's role in addressing climate change through its normative framework. The human rights approach to climate change under the African Charter on Human and Peoples' Rights (the Banjul Charter) is a viable avenue because human rights law forms the basis for states' responsibility based on human rights obligations and principles. The extraterritorial application of the Banjul Charter presents an avenue for AU institutions such as the Human Rights Commission and the African Human Rights Court to curb the effects of climate change through a human rights lens. The future of the AU is presented within the context of a set of recommendations that identify strong African regional integration as an avenue through which the AU can foster the cooperation of member states to address the consequences of climate change in the AU's and RECs' normative frameworks. General recommendations are made on the need for the international climate change regime to pay more attention to issues of funding, capacity building and technology development and transfer on the basis of the vulnerability principle and in relation to the principles of equity and common but differentiated responsibilities and respective capabilities. Also, the AU needs to strengthen its legal and institutional structures to ensure deep African integration that is capable of addressing common challenges such as the consequences of climate change.
Keywords: African Charter on Human and Peoples Rights; African Economic Community (AEC); Climate Change; EAC Treaty; ECOWAS Treaty; Human rights; International climate change regime; Normative framework; Regional integration; SADC Treaty; State cooperation; The Constitutive Act of AU

The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation